Analysing Self-Discipline: An Overview of Self-Control, Self-Regulation and Delay of Gratification in Elementary School Students in Jombang - Mahatmaharti, Rr. Agung Kesna; Prijambodo, Raden Firman Nurbudi; Dinarti, Siti (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to describe the self-discipline character of elementary school students in Jombang, in terms of delay of gratification, self-control, and self-regulation. Self-discipline is an important factor that supports students‘ learning success, as it is directly related to student's ability to organise themselves to follow school rules and achieve academic goals. Data were collected through distributing questionnaires to elementary school students spread across several schools in Jombang. The research method used was descriptive quantitative with a survey approach. This involved designing a questionnaire that measured the three aspects of self-discipline, distributing it to a representative sample of 200 students, and then analyzing the responses using descriptive statistical techniques. The results showed that primary school students in Jombang generally have a fairly good level of self-discipline. The self-control aspect shows the highest score, followed by self-regulation, while the delay of gratification aspect tends to be lower. The findings indicate that although students can control themselves and regulate their behaviour, they still need to improve in delaying gratification to achieve greater goals. The implications of this study emphasise the importance of self-discipline development programmes in primary schools that focus on self-control and behaviour regulation and improving delay of gratification. Interventions designed with attention to all three aspects can help students develop more holistic self-discipline skills, which in turn supports their future success